2020
DOI: 10.3389/fsurg.2020.616654
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects Involved in the Degeneration of Cryopreserved Arterial Allografts

Abstract: Introduction: Cryopreserved arterial allografts have remained an option in patients requiring distal revascularization or associated with vascular infection, in the absence of a valid autogenous saphenous vein. The objective of this study is to describe the different clinical, anatomopathological, and immunological findings related to vascular transplant rejection.Methods: In a prospective trial, 35 patients who underwent cryopreserved allogeneic arterial bypass were studied, including demographics and conduit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The increase in vascular segments distribution is directly related to the increase in iliac-femoral arteries for by-pass surgery. Even though graft degeneration is described in patients requiring distal revascularisation, patient outcomes and limb survival are good for clinical patient conditions who carry a high morbidity and mortality (González-Gay et al 2020 ). The total number of vascular allografts is also influenced by a decrease in the distribution of pulmonary patches used for congenital malformations, probably due the development of novel patch alternatives including biomaterials, decellularisated matrices or 3D bioprinting scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in vascular segments distribution is directly related to the increase in iliac-femoral arteries for by-pass surgery. Even though graft degeneration is described in patients requiring distal revascularisation, patient outcomes and limb survival are good for clinical patient conditions who carry a high morbidity and mortality (González-Gay et al 2020 ). The total number of vascular allografts is also influenced by a decrease in the distribution of pulmonary patches used for congenital malformations, probably due the development of novel patch alternatives including biomaterials, decellularisated matrices or 3D bioprinting scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] A more recent study showed the successful use of cryopreserved allografts in renal vessel extension in living donor kidney transplants without late vascular complications. 25 Despite these studies, a major concern is that because cryopreservation preserves living cells, donor endothelium is subject to both cell-and antibody-mediated rejection, [26][27][28][29] which may contribute to a high failure rate. Studies have demonstrated that the endothelial lining and vessel wall of venous allografts may repopulate with cells of recipient origin, although it is unclear whether changes in the anticoagulant properties of the endothelium affect its functional status.…”
Section: Discussionmentioning
confidence: 99%